Island Abdominal Skin Flap For Reconstruction Post Excision Defect Of Arterio-Venous Malformation In Labia Majora: A Case Report - Haryani, Jenny Indah; Mas’ud, Ahmad Fawzy (Jurnal Plastik Rekonstruksi, 2019)
Background : Arterio-venous malformations (AVMs) defined as high-flow vascular malformations of dysmorphic arterial and venous vessels. And connected directly to one another without an intervening capillary bed. The incidence is higher in females than male (3-5:1). Globally, there are only 5 cases of genital hemangiomas reported. Various treatment has been investigated, a recent topical treatment is the application of timolol. It has minimal adverse effects, easy administration, and good cosmetic outcomes. However, the effectiveness of timolol in vulvar cases remains unclear. Case Report : A one-year-old girl was brought by her mother with complaint of a lump in her child's genitals. The lump was appeared during the early days of her life and it was getting bigger gradually. A plastic surgeon performed excision and reconstruction procedure using the island abdominal flap technique. Discussion : Preserving vaginal function and perineal integrity is quite challenging, and cosmesis correspondingly less important. The patient underwent surgical excision and primary closure procedure in the labia majora region, followed with abdominal flap tunneled through the mons pubis. Conclusion: Surgical excision and primary closure are the most recommended procedure for overcoming genital lesion. A reconstruction using flap following the procedure resulted in a normal contour and well functioned genital.